2013
DOI: 10.1021/la4010246
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization of Ultrasonic Spray Coating of Polymer Films

Abstract: In this work we have performed a detailed study of the influence of various parameters on spray coating of polymer films. Our aim is to produce polymer films of uniform thickness (500 nm to 1 μm) and low roughness compared to the film thickness. The coatings are characterized with respect to thickness, roughness (profilometer), and morphology (optical microscopy). Polyvinylpyrrolidone (PVP) is used to do a full factorial design of experiments with selected process parameters such as temperature, distance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 28 publications
1
68
0
1
Order By: Relevance
“…A lower nozzle-to-stent distance tended to result in smoother coatings, perhaps because this led to an even flow of the coating solution on the stent surface. Similar results were reported by Bose et al (35) for polyvinylpyrrolidone ultrasonically sprayed onto a 5×20 mm area, and Shanshan et al (17) also reported that higher flow rates resulted in smoother coatings of PLGA (LA/ GA=75/25, Mw 100000) containing 5%, 7%, or 9% PEG plasticizer (to reduce PLGA cracking) and PLGA:sirolimus ratios of 2:1; 3:1; or 4:1. Shanshan also found that changing the solvent (and presumably the evaporation rate) affected roughness, a relationship which we did not observe in our study.…”
Section: Surface Roughnesssupporting
confidence: 84%
“…A lower nozzle-to-stent distance tended to result in smoother coatings, perhaps because this led to an even flow of the coating solution on the stent surface. Similar results were reported by Bose et al (35) for polyvinylpyrrolidone ultrasonically sprayed onto a 5×20 mm area, and Shanshan et al (17) also reported that higher flow rates resulted in smoother coatings of PLGA (LA/ GA=75/25, Mw 100000) containing 5%, 7%, or 9% PEG plasticizer (to reduce PLGA cracking) and PLGA:sirolimus ratios of 2:1; 3:1; or 4:1. Shanshan also found that changing the solvent (and presumably the evaporation rate) affected roughness, a relationship which we did not observe in our study.…”
Section: Surface Roughnesssupporting
confidence: 84%
“…Spray coating of PDLLA was only done on the top surface of the cantilevers. The spray coating parameters were optimized to prepare uniform and non-uniform coating on the cantilever surface with an average roughness (R a ) of about R a = 200 nm and R a < 80 nm, respectively [36]. For preparing uniform film, the nozzlesubstrate distance was 15 mm with 10 spray-passes while for non-uniform film the nozzle-substrate distance was 45 mm with 20 spray-passes.…”
Section: Spray Coatingmentioning
confidence: 99%
“…By changing the spray coating parameters [36] both uniform and non-uniform PDLLA films are deposited on the silicon cantilevers and the biodegradation of films with different surface morphologies is investigated. Image analysis of the optical microscope images is conducted to monitor the dimensions of the PDLLA coating during degradation.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,21,22 Both of these techniques require special spray coating or ink jet printing to deposit nanograms of sample. 23 Another challenge (when using microstrings or microcantilevers) is sublimation of the sample during heating. In order to overcome these difficulties, we have developed a microchannel cantilever consisting of microuidic channel integrated on top of the cantilever.…”
Section: -20mentioning
confidence: 99%